A Field Too Crowded? How Measures of Market Structure Shape Nonprofit Fiscal Health. (June 2018) - Paarlberg, Laurie E.; An, Seung-Ho; Nesbit, Rebecca; Christensen, Robert K.; Bullock, Justin
This article explores how various dimensions of market structure, often used to measure organizational crowding, affect the fiscal health of nonprofit organizations. Using 2011 National Center for Charitable Statistics (NCCS) nonprofit sector data, our findings generally support population ecology's model of a curvilinear relationship between density and days of spending. However, we also find that single dimensions of market structure do not fully capture the effects of market competition. Increasing density has a negative effect on the fiscal health of organizations in markets in which resources are more evenly distributed among actors, whereas increasing density of organizations has a positive effect on organizational fiscal health in markets in which resources are less evenly distributed among actors. These results are sensitive to different specifications of fiscal health and field of nonprofit activity.